Lis Pendens in International Litigation. - McLachlan, Campbell (Pocket Books of the Hague Academy of International Law//Les livres de poche de l'Académie de droit international de La Haye., 2009)
What legal principles apply when courts in different jurisdictions are simultaneously seised with the same dispute? This question - of international lis pendens - has long been controversial. But it has taken on new and urgent importance in our age. Globalization has driven an unprecedented rise in forum shopping between national courts and a proliferation of new international tribunals. Problems of litispendence have spawned some of the most dramatic litigation of modern times - from anti-suit injunction battles in commercial disputes, to the appeals of prisoners on death row to internationa.